Rewriting the phase diagram of a diamagnetic liquid crystal by a magnetic field - Fatin Hajjaj; Takashi Kajitani; Hiroyuki Ohsumi; Yoshikazu Tanaka; Kenichi Kato; Masaki Takata; Hideaki Kitazawa; Taka-hisa Arima; Takuzo Aida; Takanori Fukushima (Nature Communications, 2018)
Magnetically induced phase behaviour in a soft matter system is of potential interest for magneto-responsive compounds. Here the authors fabricate a discotic ionic liquid crystalline hybrid material which can be switched from orthorhombic to cubic phase in the absence or presence of a strong magnetic field.